Knowledge and Attitude on Atraumatic Care to Hospitalized Children among Nurses of a Tertiary Level Hospital in Eastern Nepal - Mahato, Pramila; Karna, Basanta Kumar; Chaudhari, Amit Kumar; Singh, Rakesh (Journal of Nursing Education of Nepal, 2022)
Background: The experience of hospitalization is usually distressing and even traumatic, especially  for children. Being hospitalized and receiving care affects the child’s response to their illness. Action  aimed at solving children’s problems by nurses must be based on atraumatic care principles. The  objective of the study was to assess the knowledge and attitude of nurses regarding atraumatic care to  hospitalized children. Methods: A descriptive cross-sectional study was conducted among 106 nurses in the tertiary hospital  in Eastern Nepal. All the nurses working in the study setting were recruited in the study. A pre-tested  semi-structured questionnaire was used to collect the data from the respondents. Obtained data were  analyzed in SPSS version 20 by using both descriptive and inferential statistics. Results: The majority (68.70%) of respondents had adequate knowledge towards atraumatic care  among hospitalized children. Similarly, more than half (52.80%) of the respondents showed favorable  attitudes in the implementation of atraumatic care. The respondents’ knowledge and attitude were not  significantly associated with selected sociodemographic variables. However, there was a significant  positive correlation between nurse’s knowledge and attitude towards the implementation of atraumatic  care. Conclusion: Despite the finding that more than two third of the nurses had adequate knowledge of the  implementation of atraumatic care, the favorable attitude towards its application among hospitalized  children seems poor. Henceforth, with the finding that a positive correlation exists between knowledge  and the attitude of nurses towards the implementation of atraumatic care, a favorable attitude of the  nurses could be enhanced by increasing knowledge regarding implementation of atraumatic care.
Keywords: Atraumatic care; attitude; knowledge; nurses